2005
DOI: 10.1095/biolreprod.104.034975
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Contributes to Vascular Lumen Formation and Vascular Branching in Human Placental Vasculogenesis1

Abstract: Placental vasculogenesis consists of several stages, including appearance of hemangioblasts and angiogenic cell islands, setting up a primitive vascular network, and transition from vasculogenesis to sprouting and nonsprouting angiogenesis. In the present study, we hypothesized that placental vasculogenesis and angiogenesis require apoptosis during the formation of primitive vascular pattern, vessel elongation, and angiogenic branching. Vasculogenesis and apoptotic cells were identified using CD31 immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…For example, high proportions of ECs lead to cluster formation accompanied or followed by apoptotic EC death. This massive cell death, which is not found in areas of EC tubular structures in the spheroid cocultures, clearly does not reflect the process of EC apoptosis found in the middle of a cord interpreted to contribute to lumen formation and maturation of patent small blood vessels (15,51). Both culture strategies applied in the present study imply an optimum fibroblast-to-EC ratio for EC attachment, survival, and network formation that is in the range of 10 to 1.…”
Section: Discussionmentioning
confidence: 59%
“…For example, high proportions of ECs lead to cluster formation accompanied or followed by apoptotic EC death. This massive cell death, which is not found in areas of EC tubular structures in the spheroid cocultures, clearly does not reflect the process of EC apoptosis found in the middle of a cord interpreted to contribute to lumen formation and maturation of patent small blood vessels (15,51). Both culture strategies applied in the present study imply an optimum fibroblast-to-EC ratio for EC attachment, survival, and network formation that is in the range of 10 to 1.…”
Section: Discussionmentioning
confidence: 59%
“…The fact that capillary-like structure formed in all groups indicates that apoptosis occuring in HUVECs does not prevent HUVECs from differentiating into capillary-like structures. Other reports have also suggested that the occurrence of apoptosis in the endothelium is required during the formation of capillary network structure, [34][35][36] since inhibition of apoptosis weakens the potential of angiogenesis by HUVECs. 37) Yilmaz recently reported that inhibition of p38 MAPK by SB203580 prevented serum starvation-induced apoptosis in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…These precursor endothelial cells are united by either desmosomes or tight junctions, and the cords gradually acquire lumens and unite to form vessels (Dempsey 1972, Demir et al 1989. The first signs of lumen formation are seen around 23 days pc, and immunohistochemical and morphological evidences suggest that apoptosis is involved in the process (Tertemiz et al 2005). Early erythrocytes, still containing a nucleus, are often seen within the newly formed lumen, having differentiated from the inner aspect of the hemangioblastic cluster.…”
Section: Morphological Aspects Of Vascular Developmentmentioning
confidence: 99%